Life on the Number Line: Routes to Understanding Fraction Magnitude for Students With Difficulties Learning Mathematics. (November 2017) - Gersten, Russell; Schumacher, Robin F.; Jordan, Nancy C.
Magnitude understanding is critical for students to develop a deep understanding of fractions and more advanced mathematics curriculum. The research reports in this special issue underscore magnitude understanding for fractions and emphasize number lines as both an assessment and an instructional tool. In this commentary, we discuss how number lines broaden the concept of fractions for students who are tied to the more general part–whole representations of area models. We also discuss how number lines, compared to other representations, are a superior and more mathematically correct way to explain fraction concepts.